Initiation of human colon cancer cell proliferation by trypsin acting at protease-activated receptor-2 - Dalila Darmoul; JC Marie; Hélène Devaud; Valérie Gratio; Marc Laburthe (2001)
The protease-activated receptor-2 (PAR-2) is a G protein-coupled receptor that is cleaved and activated by trypsin. We investigated the expression of PAR-2 and the role of trypsin in cell proliferation in human colon cancer cell lines. A total of 10 cell lines were tested for expression of PAR-2 mRNA by Northern blot and RT-PCR. PAR-2 protein was detected by immunofluorescence. Trypsin and the peptide agonist SLIGKV (AP2) were tested for their ability to induce calcium mobilization and to promote cell proliferation on serum-deprived cells. PAR-2 mRNA was detected by Northern blot analysis in 6 out of 10 cell lines [HT-29, Cl.19A, Caco-2, SW480, HCT-8 and T84]. Other cell lines expressed low levels of transcripts, which were detected only by RT-PCR. Further results were obtained with HT-29 cells: (1) PAR-2 protein is expressed at the cell surface; (2) an increase in intracellular calcium concentration was observed upon trypsin (1-100 nM) or AP2 (10-100 microM) challenges; (3) cells grown in serum-deprived media supplemented with trypsin (0.1-1 nM) or AP2 (1-300 microM) exhibited important mitogenic responses (3-fold increase of cell number). Proliferative effects of trypsin or AP2 were also observed in other cell lines expressing PAR-2. These data show that subnanomolar concentrations of trypsin, acting at PAR-2, promoted the proliferation of human colon cancer cells. The results of this study indicate that trypsin could be considered as a growth factor and unravel a new mechanism whereby serine proteases control colon tumours.